Cardiac function after exhaustive open-sea swimming - Alexiou, S.; Kouidi, E.; Fahadidou-Tsiligiroglou, A.; Karamouzis, M.; Deligiannis, A. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The present study examined the acute effects of exhaustive 25-km open-sea swimming on left ventricular (LV) function and morphology. Methods: Twenty elite male swimmers (22.3±4.1 years) participated in this study. Two-dimensionally guided M-mode echocardiograms, and electrocardiographic, phonocardiographic and carotid pulse tracings were performed simultaneously before and immediately after prolonged exhaustive swimming to evaluate the LV function and morphology, and the cardiac sympathetic outflow. Blood samples were also collected before and after the race to determine the hematocrit and the plasma concentrations of K+, Na+, Ca2+, a-ANP, renin, myoglobulin, CPK-MB, and lactate. Results: Exhaustive swimming was associated with a significant reduction in LV fractional shortening (-13%), ejection fraction (-11%), stroke volume (-25%), and LV internal diastolic diameter (-7%). In contrast, cardiac index was increased by 31%, total peripheral resistance was increased by 7%, and LV circumferential and meridional wall stresses were increased by 101% and 102%, respectively. Significant relationships were found between the increases in total peripheral resistance and LV circumferential wall stress and the decrease in ejection fraction. On the contrast, no significant relationship was found between the increased hematocrit and decreased ejection fraction. Furthermore, the pre-ejection period increased by 11%, the pre-ejection period to LV ejection time ratio increased by 15%, and the electrical to electromechanical systole relationship increased from -8 to 10 ms. Immediately after the race, there were significant increases in hematocrit (9%), and plasma concentrations of a-ANP (211%), renin (161%) and lactate (72%), myoglobulin (421%), and CPK-MB (141%) compared to pre-race values. Conclusion: In elite athletes, prolonged exhaustive swimming is associated with depressed LV function, as suggested by reduced stroke volume, ejection fraction, and LV fractional shortening. This alteration is mainly due to increased afterload.